Kondisi Sosial-Ekonomi dan Peran Masyarakat Nelayan dalam Menjaga Keberlanjutan Ekosistem Pesisir di Kampung Melayu, Kota Batam - Muhammad Hidayat; Muhammad Tuah Sakti; Perianto Ginting; Anjas Arif Sugara; Dwi Karisma Oktavia; Febri Edward (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Coastal communities have a close relationship with coastal and marine resources, particularly through fisheries and other economic activities that depend on coastal ecosystems. This study aimed to describe the socio-economic conditions of coastal communities and examine the role of fishing communities in supporting the sustainability of coastal ecosystems in Kampung Melayu, Batam City. The study employed a descriptive research design with a qualitative approach supported by quantitative descriptive data. Data were collected through observation, questionnaires, semi-structured interviews, and documentation. The respondents consisted of 10 community members selected purposively, while key informant interviews involved two fishermen and one community leader. The results showed that seven respondents (70%) worked as fishermen, two respondents (20%) worked as seafood traders, and one respondent (10%) had other occupations. The respondents ranged in age from 20 to 55 years, with educational backgrounds ranging from elementary to senior high school. The findings indicate that the socio-economic conditions of coastal communities are closely related to the availability and condition of coastal and marine resources. Community involvement in maintaining coastal ecosystems was reflected in environmental awareness, participation in conservation activities, coastal cleanliness, and support for mangrove preservation. Therefore, sustainable coastal management requires an approach that integrates environmental conservation with the socio-economic interests of local communities. Strengthening environmental education, community participation, alternative livelihood opportunities, and collaboration among local communities, universities, local governments, and other stakeholders is expected to support the long-term sustainability of coastal ecosystems.